Protective antigen–mediated delivery of an anti-CRISPR protein for precision genome editing - Axel O. Vera; Nicholas L. Truex; Vedagopuram Sreekanth; Bradley L. Pentelute; Amit Choudhary; Ronald T. Raines (Proceedings of the National Academy of Sciences, 2025)
Precise control over the dosage of Cas9-based technologies is essential because off-target effects, mosaicism, chromosomal aberrations, immunogenicity, and genotoxicity can arise with prolonged Cas9 activity. Type II anti-CRISPR proteins (Acrs) inhibit and control Cas9 but are generally impermeable to the cell membrane due to their size and anionic charge. Moreover, existing Acr delivery methods are long-lived and operate within hours (e.g., viral and nonviral vectors) or require external devices (e.g., electroporation), limiting therapeutic applications. To address these problems, we developed a protein-based anti-CRISPR delivery platform, LF N -Acr/PA, which delivers Acrs into cells within minutes. LF N -Acr/PA is a nontoxic, two-component protein system derived from anthrax toxin, where protective antigen (PA) proteins bind receptors widespread in human cells, forming a pH-triggered endosomal pore that an engineered Acr (LF N -Acr) binds and uses to enter the cell. In the presence of PA, LF N -Acr enters human cells (e.g., immortalized cell lines, embryonic stem cells, and 3D cell cultures) at concentrations as low as 2.5 pM to inhibit up to 95% of Cas9-mediated knockout, knock-in, transcriptional activation, and base editing. Timing LF N -Acr delivery reduces off-target base editing and increases Cas9 specificity by 41%. LF N -Acr/PA is the most potent known cell-permeable CRISPR-Cas inhibition system, significantly improving the utility of CRISPR for genome editing.